2014
DOI: 10.3389/fevo.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the role of structural blue and melanin-based chestnut coloration in aggressive contests in male eastern bluebirds

Abstract: Male eastern bluebirds (Sialia sialis) have feathers with either structurally based blue coloration or melanin-based chestnut coloration, and they hold territories during the breeding season that they defend vigorously. We tested whether the melanin pigmentation or structural coloration of feathers serve as signals during intrasexual aggressive encounters by placing color-modified stuffed bluebirds in male territories. We recorded the time to attack and the intensity of attacks on each model, and we then compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Eastern bluebird females did not prefer more brightly colored males in either aviary or field experiments, implying that coloration itself is not important in mate choice in this species (Liu et al 2007(Liu et al , 2009. Instead, coloration is associated with male dominance (Mercadante & Hill 2014) and correlated with a male's ability to secure a territory early in the breeding season (Siefferman & Hill 2005c). These results lend support to the idea that coloration functions primarily as a social signal in bluebirds and that assortative mating patterns result from brighter males and females If brighter pairs hold better territories, one might also predict that such pairs would successfully fledge more offspring.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Eastern bluebird females did not prefer more brightly colored males in either aviary or field experiments, implying that coloration itself is not important in mate choice in this species (Liu et al 2007(Liu et al , 2009. Instead, coloration is associated with male dominance (Mercadante & Hill 2014) and correlated with a male's ability to secure a territory early in the breeding season (Siefferman & Hill 2005c). These results lend support to the idea that coloration functions primarily as a social signal in bluebirds and that assortative mating patterns result from brighter males and females If brighter pairs hold better territories, one might also predict that such pairs would successfully fledge more offspring.…”
Section: Discussionmentioning
confidence: 86%
“…, ). Instead, coloration is associated with male dominance (Mercadante & Hill ) and correlated with a male's ability to secure a territory early in the breeding season (Siefferman & Hill ). These results lend support to the idea that coloration functions primarily as a social signal in bluebirds and that assortative mating patterns result from brighter males and females defending better territories rather than mate choice on ornaments per se.…”
Section: Discussionmentioning
confidence: 99%
“…In males, sexual selected colors may arise due to female mate-choice for signals of phenotypic or genetic quality (Hill 1991;McGraw 2003;Safran & McGraw 2004) or because males use these signals to mediate same-sex interactions (Andersson 1994;Pryke & Griffith 2006). These status signals may indicate social rank, age, or fighting ability (Fugle et al 1984;Senar 2006;Mercadante & Hill 2014), such that subordinate individuals benefit from not challenging dominant individuals in contests they would likely lose and dominant individuals benefit from not allocating energy and time to engaging with individuals of lower quality (Rohwer 1975;Hawkins et al 2012;Mercadante & Hill 2014;Young et al 2015). These status signals may indicate social rank, age, or fighting ability (Fugle et al 1984;Senar 2006;Mercadante & Hill 2014), such that subordinate individuals benefit from not challenging dominant individuals in contests they would likely lose and dominant individuals benefit from not allocating energy and time to engaging with individuals of lower quality (Rohwer 1975;Hawkins et al 2012;Mercadante & Hill 2014;Young et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These status signals may indicate social rank, age, or fighting ability (Fugle et al 1984;Senar 2006;Mercadante & Hill 2014), such that subordinate individuals benefit from not challenging dominant individuals in contests they would likely lose and dominant individuals benefit from not allocating energy and time to engaging with individuals of lower quality (Rohwer 1975;Hawkins et al 2012;Mercadante & Hill 2014;Young et al 2015). Yet, it is beneficial for individuals to reliably signal information to rivals about their competitive ability and resource holding potential (their likelihood of winning physical altercations ;Parker 1974) to avoid risky and unnecessary confrontations in these contexts (Pryke et al 2001;Vedder et al 2010;Mercadante & Hill 2014). Yet, it is beneficial for individuals to reliably signal information to rivals about their competitive ability and resource holding potential (their likelihood of winning physical altercations ;Parker 1974) to avoid risky and unnecessary confrontations in these contexts (Pryke et al 2001;Vedder et al 2010;Mercadante & Hill 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studying single ornamental traits may provide misleading results if receivers incorporate multiple ornaments into an integrated signal (Hegyi et al 2015) or if they consider the congruence among multiple ornaments during assessment of a conspecific (Tibbetts and Izzo 2010). As a result, several recent studies have examined the relationship between different plumage ornaments within the same species (Chaine and Lyon 2008, Chaine et al 2011, Laucht and Dale 2012, Mercadante and Hill 2014, Hegyi et al 2015. In general, these studies have found that multiple ornaments may provide a varying amount of overlap in information content (Laucht and Dale 2012), with some sets of ornaments showing high covariation and functioning as a single signal, and other sets signaling different aspects of quality that are unrelated to one another.…”
Section: Introductionmentioning
confidence: 99%